Breast cancer‐derived K172N, D301V mutations abolish Na+/H+ exchanger regulatory factor 1 inhibition of platelet‐derived growth factor receptor signaling. Issue 20 (5th September 2013) - Cheng, Shan; Li, Yang; Yang, Ying; Feng, Duiping; Yang, Longyan; Ma, Qian; Zheng, Shuai; Meng, Ran; Wang, Shuhui; Wang, Songlin; Jiang, Wen G.; He, Junqi
Abstract : Na + /H + exchanger regulatory factor 1 (NHERF1) is a scaffold protein known to interact with a number of cancer‐related proteins. nherf1 Mutations (K172N and D301V) were recently identified in breast cancer cells. To investigate the functional properties of NHERF1, wild‐type and cancer‐derived nherf1 mutations were stably expressed in SKMES‐1 cells respectively. NHERF1‐wt overexpression suppressed the cellular malignant phenotypes, including proliferation, migration, and invasion. nherf1 Mutations (K172N and D301V) caused complete or partial loss of NHERF1 functions by affecting the PTEN/NHERF1/PDGFRβ complex formation, inactivating NHERF1 inhibition of PDGF‐induced AKT and ERK activation, and attenuating the tumor‐suppressor effects of NHERF1‐wt. These results further demonstrated the functional consequences of breast cancer‐derived nherf1 mutations (K172N and D301V), and suggested the causal role of NHERF1 in tumor development and progression. Abstract : NHERF1‐wt overexpression reversed the malignant phenotypes of cancer cells. nherf1 Mutations (K172N and D301V) were recently identified in breast cancer cells. nherf1 Mutations affected the PTEN/NHERF1/PDGFRβ complex formation. nherf1 Mutations inactivated NHERF1 inhibition of AKT and ERK activation. nherf1 Mutations were the causal role of NHERF1 in tumor development and progression.